SYMPTOMS OF TUBERCULOSIS IN HIV POSITIVE CHILDREN AND THE IMPACT OF PREVENTION ON THE DEVELOPMENT AND COURSE OF THE DISEASE - E. Yu. Zorkaltseva; L. V. Zaritskaya; S. V. Pugacheva (Туберкулез и болезни лёгких, 2019)
The objective of the study: to compare the clinical and X-ray signs of tuberculosis in HIV positive and HIV negative children, to identify factors that are more common in HIV infected children in the region with a high prevalence of both infections. Subjects and methods. 264 children with tuberculosis, and 41 children with HIV infection and tuberculosis undergoing inpatient treatment were enrolled in the study, which was the retrospective study of medical records. The patients underwent standard clinical and X-ray examinations, and microbiological tests. Results. Disseminated forms of tuberculosis (39.1%), tuberculous meningoencephalitis (4.9%) were more frequent in the HIV positive children, while in HIV negative children, it made 1.9 and 0.4% respectively. Among HIV positive children, 34% had several sites of tuberculosis, and 19.5% suffered from generalized forms. In HIV positive children, tuberculosis was more often detected in the infiltration phase, it was accompanied by severe intoxication symptoms, while when taking anti-tuberculosis therapy in combination with ART, they had more rapid positive changes.